Inflammatory Waldenström's macroglobulinaemia: A French monocentric retrospective study of 67 patients. (8th April 2022) - Elessa, Dikelele; Debureaux, Pierre‐Edouard; Villesuzanne, Camille; Davi, Frederic; Bravetti, Clotilde; Harel, Stephanie; Talbot, Alexis; Oksenhendler, Eric; Malphettes, Marion; Thieblemont, Catherine; Moatti, Hannah; Maarek, Odile; et al.
Summary: Waldenström's macroglobulinaemia (WM) is a B‐cell neoplasm resulting from bone marrow lymphoplasmacytic infiltration and monoclonal IgM secretion. Some patients present concomitant inflammatory syndrome attributed to the disease activity; we named this syndrome inflammatory WM (IWM). We retrospectively analysed all WM patients seen in a single tertiary referral centre from January 2007 to May 2021, and after excluding aetiologies for the inflammatory syndrome using a pertinent blood workup, including C‐reactive protein (CRP), and imaging, we identified 67 (28%) IWM, 166 (68%) non‐IWM, and nine (4%) WM with inflammatory syndrome of unknown origin. At treatment initiation, IWM patients had more severe anaemia (median Hb 90 vs 99 g/l; p  < 0.01), higher platelet count (median 245 vs 196 × 109/l; p  < 0.01) and comparable serum IgM level (median 24.9 vs 23.0 g/l; p  = 0.28). A positive correlation was found between inflammatory and haematological responses (minimal response or better) (odds ratio 32.08; 95% confidence interval 8.80–98.03; p  < 0.001). Overall survivals (OS) were similar (median OS: 17 vs 20 years; p  = 0.11) but time to next treatment (TNT) was significantly shorter for IWM (TNT1: 1.6 vs 4.8 years, p  < 0.0001). IWM mostly shared the same presentation and outcome as WM without inflammatory syndrome.